Potential and Natural Cyanide Poison for Children: Apricot Kernels - Osman Yeşilbaş (Journal of Pediatric Emergency and Intensive Care Medicine, 2019)

(untitled)
Apricot kernels contain a significant amount of amygdaline, one of the cyanogenic glycosides. In Turkey, most cases of cyanide intoxication in children are related to ingestion of apricot kernels. In this manuscript, we present two pediatric cases of cyanide intoxication presenting with vomiting and loss of consciousness after ingestion of unknown amount of fresh apricot kernels. Two patients were discharged with cure after supportive treatment without the need for cyanide antidote administration. Our report of two cases aims to raise awareness amongst the general population and health workers of the potential risk of cyanide poisoning associated with the consumption of apricot kernels. Cyanide poisoning should be kept in mind for patients with sudden loss of consciousness, high anion gap metabolic acidosis and lactic acidosis.